1990
DOI: 10.1007/bf00170582
|View full text |Cite
|
Sign up to set email alerts
|

A method for removal of toxic chromium using dialysis-sac cultures of a chromate-reducing strain of Enterobacter cloacae

Abstract: A method for removal of toxic hexavalent chromium (chromate: CrO2-4) was developed by use of dialysis-sac cultures of a chromate-reducing strain of Enterobacter cloacae (HO1). E. cloacae strain HO1 cells were put in dialysis (semipermeable membrane) sacs, and the sacs were submerged in water containing toxic CrO2-4. The dialysis sacs allowed CrO2-4 to diffuse into the culture, and CrO2-4 was reduced anaerobically in the dialysis sacs by the E. cloacae cells. Because reduced chromium readily formed insoluble ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 5 publications
2
31
0
Order By: Relevance
“…Thus, all subsequent experiments were conducted at 37°C in media with pH 7.0. These data are consistent with previously reported [13] optimum pH and temperature for Enterobacter cloacae ranging from 7.0-8.0 and 30-37°C respectively. Wang et al [43] reported that reduction of Cr(VI) by E. cloacae occurred at pH 6.5 to 8.5 and it was strongly inhibited at pH 5.0.…”
Section: Effect Of Temperature and Ph On Bacterial Growthsupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, all subsequent experiments were conducted at 37°C in media with pH 7.0. These data are consistent with previously reported [13] optimum pH and temperature for Enterobacter cloacae ranging from 7.0-8.0 and 30-37°C respectively. Wang et al [43] reported that reduction of Cr(VI) by E. cloacae occurred at pH 6.5 to 8.5 and it was strongly inhibited at pH 5.0.…”
Section: Effect Of Temperature and Ph On Bacterial Growthsupporting
confidence: 93%
“…The strain E. cloacae B2-DHA exhibited a MIC higher than 1000 µg/mL of K2CrO4 which is an indication that this strain is resistant to very high concentrations of chromate than that reported previously by Komori et al, [13] Yamamoto et al, [14] Clark, [15] Rege et al, [16] and…”
Section: Minimum Inhibitory Concentration (Mic) Of Chromatementioning
confidence: 56%
See 2 more Smart Citations
“…But they require large quantities of chemical reagents and high amount of energy [7]. Several treat ment processes have be en s ug geste d f or th e r e mo val of h e av y met als fro m a qu eou s waste streams: adsorption, biosorption, ion exchange, chemical precip itation and electrochemical methods: electrowinning, electrodialysis, electrodeionization, memb rane-less electrostatic shielding, electrodialysis and electrocoagulation which are h ighly expensive.…”
Section: Introductionmentioning
confidence: 99%